Thinking through the Death of God - Rodkey, Christopher Demuth (The journal for cultural and religious theory, 2005)
A review of Thinking Through The Death of God: A Critical Companion to Thomas J.J. Altizer, eds. Lissa McCullough and Brian Schroeder. SUNY Series in Theology and Continental Thought. Douglas Donkel, ser. ed. Albany, NY: SUNY, 2004. xxix + 254 pp. ISBN 0-7914-6219-6 (hardcover, $73.50); 0-7914-6220-X (paper, $24.95)